2020
DOI: 10.2196/16484
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Doctor Characteristics That Determine the Use of Teleconsultations in the Catalan Public Health System: Retrospective Descriptive Cross-Sectional Study

Abstract: Background eConsulta is a tele-consultation service involving doctors and patients, and is part of Catalonia's public health information technology system. The service has been in operation since the end of 2015 as an adjunct to face-to-face consultations. A key factor in understanding the barriers and facilitators to the acceptance of the tool is understanding the sociodemographic characteristics of general practitioners who determine its use. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…However, the 108 participants can be seen as a representative sample of the professionals who use telemedicine in this area, since it is not expected that many more professionals use it, although the exact number has not been recorded. Considering that nurses make up almost half of the sample, the socio-demographic profile of the participants is quite similar to that shown by analyses of primary care professionals in Catalonia [32].…”
Section: Limitationssupporting
confidence: 60%
“…However, the 108 participants can be seen as a representative sample of the professionals who use telemedicine in this area, since it is not expected that many more professionals use it, although the exact number has not been recorded. Considering that nurses make up almost half of the sample, the socio-demographic profile of the participants is quite similar to that shown by analyses of primary care professionals in Catalonia [32].…”
Section: Limitationssupporting
confidence: 60%
“…In addition, 84.88% (187,569/220,981) of the conversations had a general practitioner as the clinical interlocutor, with the others being nurses (14.31%, 31,622/220,981) or other professionals such as pediatricians and gynecologists. The characteristics of professionals that use eConsulta were previously reported, demonstrating an age range of the general practitioners of 45-54 years, who scored higher than the 80th percentile on the quality of care index, had a high degree of accessibility, involved in teaching, and work on a health team in a high socioeconomic urban setting [ 3 ]. Messages and their respective subject lines had an average length of 231 and 18 characters, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decade, telemedicine services have been introduced in the public health care systems of several industrialized countries. In Catalonia, eConsulta is an asynchronous teleconsultation service that has been integrated into the program of computerized medical records of primary care of the public health system [ 3 ]. The service was introduced in 2015 and was gradually phased in until 2017, when it became established as a service available to all primary care teams as a complement to face-to-face care.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that some studies question the efficiency of teleconsultations between primary care professionals and citizens [ 7 ], several studies suggest that the eConsulta tool helps to reduce the number of face-to-face visits [ 4 , 6 ], which may be one of the drivers of its growing use among users. With regard to the health care professionals that use eConsulta, a previous analysis found that doctors who use eConsulta are typically in the 45-64 years age group, score higher than the 80th percentile on the Quality of Care Index, have a high degree of accessibility, are involved in teaching, and work as part of a health team in a high socioeconomic urban setting [ 15 ]. With regard to eConsulta users, it is vital to analyze their characteristics in order to provide a service that is appropriate and adjusted to their needs and to also understand who is being covered by this service (and who is not) during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%